IoT-Based Humidity Control System for Electrospinning - Hikamiah, Luluk Arifatul; Ariyanto, Dewa Pascal; Widayani, Della Astri; Nugroho, Panji Setyo; Amaratirta, Jasmine Cupid; Harjunowibowo, Dewanto; Rezeki, Yulianto Agung (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2024)
In recent years, electrospinning has become the most common and most widely used nanofiber manufacturing method. One parameter affecting the manufacturing process is the humidity parameter, which affects the morphology. The control tools that have been developed have not been equipped with a remote control and monitoring system. This research aims to develop a humidity control system that can be controlled and monitored remotely and is equipped with data recapitulation. This research used methods from literature studies on humidity control systems, manufacture and assembly of hardware and software, calibration, and performance tests. A humidity control device is produced using a NodeMCU microcontroller connected to the IoT-based Blynk application. This can be controlled and monitored manually with an LCD and Keypad or by using a handphone through the Blynk application, and the humidity value can be recapitulated with Google Sheets in real-time. The sensor used for reading this humidity value is a DHT 22 sensor which has an accuracy value of 99.72% and a precision of 98.81% for 45%-95% humidity. This IoT-based humidity control system device can automate the process of controlling, monitoring, and recapitulating humidity data in real-time.